EFEK IRIGASI TUNGGAL LARUTAN TETRASIKLIN HCl 10% SETELAH SKELING DAN PENGHALUSAN AKAR TERHADAP PERUBAHAN KLINIS PERIODONTITIS KRONIS POKET 4-6 MM - Natalina Natalina; Irene Sukardi; Yuniarti Yuniarti (Faculty of Dentistry, Universitas Indonesia, 2015)
Chronic adult periodontitis (CAP) is the most common type of periodontal disease. Treatment of moderate CAP has primarily been directed at the physical removal of bacterial plaque, calculus and contaminated cementum by scaling and root planing (SRP) with or without surgical access. Irrigation solutions reach the apical portion of the pocket has flushing action properties and easy to apply. Tetracycline HCl (TTC HCl) solutions demonstrated its antimicrobial activity against subgingival microflora, shown to be substantive to dentin surface and subsequently released in active form, also has anti-collagenase properties. This study evaluates the clinical outcomes of treatment with locally TTC HCl 10% irrigation as an adjunct to SRP in subset of moderate CAP patients. The data examined were obtained from 24 patients. All patient were scaled and root planed prior to baseline measurement. The patients were monitored by parameters ; bleeding on probing (BOP), probing pocket depth (PPD), and attachment loss (LA). 56 contralateral surface exhibiting residual pocket depths 4-6mm were randomly assigned as test or control sites. After baseline measurement, each subgingival root surface was irrigated with approximately 10ml for 1 minute either with TTC HCl 10% solution (test), or Aquabides solution (control). The clinical parameters were assessed at baseline and weeks 3. The two sites resulted in significant statistical and clinical improvement in all parameters. BOP was not significantly reduced in test site compared to control site. PPD and LA was significantly reduced at test site compared to control site. The result indicate that subgingival irrigation with TTC HCl 10% solution 10ml for 1 minute may have a role in the management of moderate CAP. This treatment reduces surgical needs.